Emphatic Tones as a Means of Expressing Positive (Positive) and Negative (Negative) Shades of Meaning - Gunel Jalilova (Zien Journals, 2022)
To understand oral speech, the listener attaches great importance to understanding prosodic signals (intonation, voice timbre, range of voice, stress, rhythm) and non-verbal means of communication (gestures, facial expressions, eye contact). The nature of such intonation is easier to understand in the interaction between gestures, facial expressions and eye contact, which are non-verbal means of communication. In the literature one can find the views and experience of a number of linguists on this issue.
Keywords: emphatic tones; rise-fall metaphor